Exploring the protein stabilizing capability of surfactants against agitation stress and the underlying mechanisms - Zöller, Michelle; Hafiz, Supriyadi; Marx, Andreas; Erwin, Nelli; Fricker, Gert; Carpenter, John F. (Journal of pharmaceutical sciences, 2022)
The application of surfactants in liquid protein formulation is a common practice to protect proteins from liquid-air interface-induced protein aggregation. Typically, Polysorbate 20 or 80 are used, but degradation of these surfactants can result in particle formation and/or protein degradation. The purpose of the current study was to directly compare three alternative protein stabilizing molecules - Poloxamer 188, hydroxypropyl-cyclodextrin and a trehalose-based surfactant - to Polysorbate 80 for their capacities to reduce agitation-induced protein aggregation and particle formation; and furthermore, investigate their underlying protein stabilizing mechanisms. To this end, a small-volume, rapid agitation stress approach was used to quantify the molecules’ abilities to stabilize two model proteins. This assay was presented to be a powerful tool to screen the protein stabilizing capability of surfactants using minimum of material and time. SEC, turbidity measurements and particle analysis showed an efficient protein stabilization of all tested surfactants as well as cyclodextrin. STD-NMR and dynamic surface tension measurements indicated the competitive surface adsorption to be the main protein stabilizing mechanism of the three surfactants tested. It might also play a role to some extent in the protein stabilization by HPβCD. However, additional mechanisms might also contribute to protein stabilization leaving room for further investigations.
Dateiversion vom 15. November 2022
Gesehen am 08.02.2023